PENGARUH ELECTRONIC WORD OF MOUTH, DUKUNGAN SELEBRITAS, DAN PEMASARAN MEDIA SOSIAL TERHADAP MINAT BELI DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi Pada Produk Fashion Levi’s di Kota Semarang) - Rafif Hidayatullah, Muhammad; Dirgantara, I Made Bayu (Diponegoro Journal of Management, 2018)
Today, many companies use social media as a way to marketing their products. Levi's is one of company that utilizes social media in marketing its products. One of the social media used by Levi's in marketing its products through social media is instagram. This research aims to examine the effect of variable’s electronic word of mouth, celebrity endorsement, and social media marketing on purchase intention with brand image as the intervening variable.This research employs a purposive sampling technique on 120 respondents. The study is conducted on consumers who know the Levi's brand, have an instagram account and know or follow account @levis_indonesia in Semarang city The method used is Structural Equation Model with AMOS 24.0 Software. The results of this research show that electronic word of mouth, celebrity endorsement, and social media marketing have a positive effect on the variables of brand image intervening and intervening variables have a positive and significant influence on purchase intention